2008
DOI: 10.1097/qad.0b013e3282f57f7a
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of X4 usage among HIV-1 subtype C: evidence for an evolving epidemic in South Africa

Abstract: This study investigated the genotype and phenotype of HIV-1 isolates of 20 South African AIDS patients. We found the highest percentage of CXCR4 usage among primary isolates, in which 30% efficiently utilized CXCR4 and exhibited the syncytium-inducing phenotype. Phylogenetic analysis of env confirmed that 19 of the 20 were subtype C, and syncytium-inducing viruses had genetic changes in the V3 loop, characteristic of CXCR4 usage. Results imply that the frequency of CXCR4-utilizing subtype C is increasing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 15 publications
2
46
3
Order By: Relevance
“…HAART-naive subjects described in Connell et al, 15 are not statistically significant ( p = 1.0). Patients described in both studies were recruited from Gauteng province.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…HAART-naive subjects described in Connell et al, 15 are not statistically significant ( p = 1.0). Patients described in both studies were recruited from Gauteng province.…”
mentioning
confidence: 81%
“…21 Seclén et al 23 showed an overall concordance of 88% between PSSM and geno2pheno. Reanalysis of the Connell et al 15 data using the two algorithms showed 100% concordance of genotype with phenotype for PSSM sinsi and 95% with geno2pheno. Hence, based on concordant results from the two most widely used algorithms, a minimum of 29% of HAART-failing patients in our study had X4-utilizing viruses.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HIV-1 subtypes may exhibit phenotypic differences. Subtypes are believed to impact on tropism, with some studies associating increased CXCR4 usage with infections with subtype C (Johnston et al, 2003;Connell et al, 2008), and others finding decreased CXCR4 usage in subtype C infections (Bjorndal et al, 1997;Abebe et al, 1999;Peeters et al, 1999;Esbjornsson et al, 2010). Subtypes may have an important effect on transmission of HIV-1, as the subtype B was associated with homosexual transmission and the subtype C with heterosexual transmission (van Harmelen et al, 1997;van Harmelen et al, 2001), but a heterosexually driven subtype B epidemic has been observed in Trinidad and Tobago (Cleghorn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%